Menjembatani Infrastruktur Teknologi, Kapabilitas Bisnis, dan Perilaku Konsumen dalam Metaverse: Tinjauan Literatur Integratif dan Kerangka Technology-Business-Consumer-Governance (TBCG) - oscar chrismadian (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Metaverse research has expanded rapidly, yet its knowledge base remains fragmented into three streams that are rarely connected explicitly: technological architecture, business applications, and consumer responses. This article develops a cross-level synthesis by integrating three complementary reviews: a technology landscape analysis based on 2,451 documents, a review of metaverse research across business functions based on 29 documents, and a consumer behavior review based on 48 empirical articles. The study adopts an integrative review or review-of-reviews design. Evidence was extracted according to scope, methods, technologies, business functions, theoretical lenses, experience characteristics, outcomes, and research gaps, and was analyzed through comparative thematic synthesis. The findings indicate that AR/VR/XR, artificial intelligence, blockchain and NFTs, digital twins, sensors, and low-latency connectivity do not automatically create value. These technologies first generate affordances such as immersion, presence, embodiment, persistence, and interactivity, which must be orchestrated through dynamic capabilities and cross-functional business integration. Consumer responses emerge through cognitive, affective, social-identity, and risk-trust mechanisms. Privacy, security, digital ownership, interoperability, accessibility, and regulation operate as boundary conditions that shape sustainable value creation. Based on this synthesis, the article proposes the Technology-Business-Consumer-Governance (TBCG) framework, six conceptual propositions, and a research agenda emphasizing actual behavior, longitudinal and experimental designs, emerging-economy contexts, small and medium enterprises, and inclusive governance. The framework moves metaverse research beyond technological determinism toward a multilevel and responsible account of value creation.